2018
DOI: 10.1159/000488481
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid BACE1 Activity and sAβPPβ as Biomarker Candidates of Alzheimer’s Disease

Abstract: Background/Aims: The utility of β-site amyloid-β precursor protein (AβPP) cleaving enzyme 1 (BACE1) activity and soluble AβPP β (sAβPPβ) levels in cerebrospinal fluid (CSF) in detecting Alzheimer’s disease (AD) is still elusive. Methods: BACE1 activity and sAβPPβ concentration were measured in patients with AD dementia (n = 56) and mild cognitive impairment (MCI) due to AD (n = 76) with abnormal routine AD CSF markers, in patients with MCI with normal CSF markers (n = 39), and in controls without preclinical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…Although it might be challenging to establish from post-mortem tissue whether a specific change is a late or early event or an epiphenomenon in disease pathogenesis 24 , Cole et al showed that BACE1 elevation was correlated with amyloid pathology in mouse models both in the absence (model: Tg2576) and presence (5XFAD) of significant neuronal loss 24,25 . In agreement with an early involvement of BACE1 in LOAD, enzyme activity was found to be higher in CSF and plasma of MCI converters compared to non-converters 16,18,26 .…”
Section: Discussionsupporting
confidence: 78%
“…Although it might be challenging to establish from post-mortem tissue whether a specific change is a late or early event or an epiphenomenon in disease pathogenesis 24 , Cole et al showed that BACE1 elevation was correlated with amyloid pathology in mouse models both in the absence (model: Tg2576) and presence (5XFAD) of significant neuronal loss 24,25 . In agreement with an early involvement of BACE1 in LOAD, enzyme activity was found to be higher in CSF and plasma of MCI converters compared to non-converters 16,18,26 .…”
Section: Discussionsupporting
confidence: 78%
“…The generation of Aβ monomeric forms is dependent upon the activity of BACE1, this being directly related to synaptic functions, plasticity and homeostasis [ 69 , 72 ]. Studies have shown the significantly increased concentrations and activity rates of BACE1 in AD brains and CSF, which is thought to cause a vicious cycle by producing Aβ peptides near synapses [ 69 , 72 , 73 , 74 , 75 ]. Other synaptic dysfunction-associated biomarkers for AD include synaptotagmin, a calcium sensor protein, SNAP-25, a component of the soluble N-ethylmaleimide sensitive factor attachment protein receptor complex, GAP-43, a pre-synaptic membrane protein, and synaptophysin, which has exhibited increased levels in the CSF of AD patients [ 69 , 76 ].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…In this context, Rosen and colleagues found that BACE1 activity was significantly increased in AD patients with mild dementia compared to patients at more severe stages [12]. A recent study showed that BACE1 biomarker candidates are significantly increased in individuals with MCI, but not with ADD, when compared with the HC group [13]. Therefore, it is likely that the disease stage of the individual patient may influence BACE1 concentration and activity, and thus, clinical heterogeneity of included individuals may have neutralized inter-group differences.…”
Section: Potential Explanation Of Controversial Results In Csf (And Bmentioning
confidence: 98%
“…Most of the recent studies used CSF core biomarkers of AD, where BACE1 correlated indeed with Aβ and tau markers. In particular, Mulder and colleagues found that BACE1 activity was increased in individuals showing characteristic AD biological features compared to individuals with negative AD biomarkers [16], while Alexopoulos and colleagues showed significantly decreased CSF BACE1 activity in individuals with MCI without AD pathophysiology compared to patients with MCI due to AD [13].…”
Section: Potential Explanation Of Controversial Results In Csf (And Bmentioning
confidence: 99%